2023
DOI: 10.1177/00315125231216020
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Athletes’ Self-Presentations on Social Media and Their Self-Esteem as Moderated by Their Perceptions of Responsiveness by Others

Kyoungjin Yang,
Sungho Kwon,
Dojin Jang

Abstract: Social media has been an increasingly utilized communication tool, and it has gained popularity among adolescent athletes. Our aim here was to investigate whether a positive and honest self-presentation on social media increased adolescent athletes' self-esteem, and we examined the moderating effect of perceived responsiveness. After receiving informed consent of participants and their parents/legal guardians, we recruited 468 adolescent athletes/participants (244 males, 224 females; Mage = 15.39 years, SD = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
1
0
1
Order By: Relevance
“…The research on social norms and self-representations of young Finns on Facebook and Last.fm found that the participants usually pursued the identical socio-cultural objective -presentation of authenticity . Another positive example is the study establishing a statistically significant correlation of honest presentation in social networks with junior athletes' self-esteem (Yang et al, 2024). Unlike the above studies, S. Balanji et al (2023) researched creation of another account on "Instagram" with low rates for authentic self-presentation which is usually called Finsta D. Paulhus (2002) у авторській методиці феномен соціальної бажаності вимірює двома шкалами -"самообман" і "управління враженнями".…”
Section: Antonina Hrys* Oksana Pavliukmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on social norms and self-representations of young Finns on Facebook and Last.fm found that the participants usually pursued the identical socio-cultural objective -presentation of authenticity . Another positive example is the study establishing a statistically significant correlation of honest presentation in social networks with junior athletes' self-esteem (Yang et al, 2024). Unlike the above studies, S. Balanji et al (2023) researched creation of another account on "Instagram" with low rates for authentic self-presentation which is usually called Finsta D. Paulhus (2002) у авторській методиці феномен соціальної бажаності вимірює двома шкалами -"самообман" і "управління враженнями".…”
Section: Antonina Hrys* Oksana Pavliukmentioning
confidence: 99%
“…соціокультурну мету -презентацію автентичності . Також позитивним прикладом є з'ясування статистично достовірного зв'язку чесної презентації в соціальних мережах із самооцінкою юних спортсменів (Yang et al, 2024). На відміну від представлених досліджень, S. Balanji et al (2023) вивчали створення другого облікового запису "Instagram" із низькими ставками для автентичної самопрезентації, який зазвичай називають Finsta (комбінація "Fake" та "Instagram").…”
Section: Antonina Hrys* Oksana Pavliukunclassified